2017
DOI: 10.5603/imh.2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

Risk-taking behaviours among fishermen in Morocco by the evaluation of “ordalique” functioning

Abstract: no-ordalique ones: tobacco (54.5% vs. 48.6%, p < 0.035), alcohol (42.8% vs. 32.4%, p < 0.0001), cannabis (34.8% vs. 26.6%, p < 0.0001), psychotropic drugs (13.8% vs. 10.4%, p < 0.081) and a combination of toxic habits (27.7% vs. 19.6%, p < 0.0001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In our study, the prevalence of tobacco smoking was 46.6%, cannabis smoking 29.9% and alcohol consumption 38.3%. Two other surveys [15,16], the first relating to risk behaviours and the second to the consumption of addictive substances among Moroccan fishermen, showed similarly high rates of tobacco smoking (58.5% and 52.3%), cannabis smoking (36.2% and 31.7%) and alcohol consumption (36.5% and 38.9%). These prevalences are significantly higher than the general male population over the age of 20, which are respectively 34.5%, 9% and 14% [13].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In our study, the prevalence of tobacco smoking was 46.6%, cannabis smoking 29.9% and alcohol consumption 38.3%. Two other surveys [15,16], the first relating to risk behaviours and the second to the consumption of addictive substances among Moroccan fishermen, showed similarly high rates of tobacco smoking (58.5% and 52.3%), cannabis smoking (36.2% and 31.7%) and alcohol consumption (36.5% and 38.9%). These prevalences are significantly higher than the general male population over the age of 20, which are respectively 34.5%, 9% and 14% [13].…”
Section: Discussionmentioning
confidence: 88%
“…In these countries, risk-taking behaviour among artisanal fishermen is still an observational epidemiological reality, associated with significant morbidity and mortality. These dangerous behaviours are very diverse and include high prevalence of psychoactive substance use [15,16]. Addictive behaviours (particularly smoking tobacco and cannabis) are very common among the fishermen who suffer of health problems and poor access to healthcare utilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence among handlers was as high as in administrative staff on land working in the maritime sector: 39.5% for tobacco smoking, 15.5% for cannabis, and 28.6% for alcohol. They were significantly lower than among Moroccan fishermen [10]. Three studies conducted in this population in 2014, 2016 and 2017 showed 58.8%, 52.3% and 46.6% for tobacco smoking respectively, 36.2%, 31.7% and 37.4% for cannabis smoking and 36.5%, 38.9% and 42.5% for alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of toxic habits is constantly increasing in developing countries and all occupational sectors are affected [2][3][4][5][6][7][8][9][10]. All psychoactive substances cause a disorder of alertness, a change in the perception of risk and/or an increased risk-taking with consequences in terms of public health, occupational medicine, and safety at workplace [11].…”
mentioning
confidence: 99%